2008
DOI: 10.4141/cjps07063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term burn-pruning on the flora in a lowbush blueberry (Vaccinium angustifolium Ait.) stand

Abstract: . 2008. Effect of long-term burn-pruning on the flora in a lowbush blueberry (Vaccinium angustifolium Ait.) stand. Can. J. Plant Sci. 88: 351Á362. The effect of burn-pruning on the flora in a natural stand of lowbush blueberry was studied over a 24-yr period in Newfoundland and Labrador, Canada. Treatments were: not burned and burn-pruned every 2nd, 3rd, or 4th year. A vegetative survey was conducted before burning and periodically in succeeding years. Following statistical analyses, species were grouped accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, two previous studies of shrubland and forest fires found no recovery of E. nigrum over periods of 4–5 yr post‐burning (Penney et al. ; Hekkala et al. ).…”
Section: Discussionmentioning
confidence: 92%
“…However, two previous studies of shrubland and forest fires found no recovery of E. nigrum over periods of 4–5 yr post‐burning (Penney et al. ; Hekkala et al. ).…”
Section: Discussionmentioning
confidence: 92%
“…Certain species of predatory ground beetles consume F. filiformis seeds in lowbush blueberry fields (Cutler et al ., ), and management practices that support the presence of these insects may therefore contribute to significant F. filiformis seed losses to predation. Festuca filiformis seeds are also susceptible to heat (White & Boyd, ), and although burn pruning does not consistently reduce F. filiformis density (Penney et al ., ), the location of most seeds on the soil surface suggests that burn pruning may be an effective method of seedbank management for these grasses. It is unclear why seedling density, but not seed density, was affected by site, although viability of F. filiformis seeds is variable (White & Kumar, ) and the difference in seedling density at each site may simply be reflective of this characteristic of seeds of this weed in lowbush blueberry fields.…”
Section: Discussionmentioning
confidence: 99%
“…Penney et al (2008) reported a large increase in R. acetosella following burning of wild blueberry fields in Newfoundland. However, subsequent burnings reduced the occurrence of R. acetosella, presumably due to destruction of seed in the soil seed bank.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 97%
“…In New Brunswick, it is associated with understory plant communities of jack pine mixed hardwood forests (MacLean and Wein 1977), and as a common weed of cereal crops (Thomas et al 1994). Rumex acetosella is also commonly associated with lowbush blueberry fields in New Brunswick, Nova Scotia (McCully et al 1991;Jensen and Yarborough 2004), and Newfoundland (Penney et al 2008). …”
Section: Habitatmentioning
confidence: 97%